The study of some physical and chemical characteristics in drinking water treatment plant of Jurf Al- Sakar subdestric in Babylon governorate, Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
Some physical and chemical characteristics of Jurf Al- Sakar drinking water plant in Babylon governorate have been studied. Seven locations for this plant were selected. These were the drinking water treatment plant source on Euphrates River before entering the plant, precipitation, filtration and collection tanks, and also after leaving the plant at distances of one meter, 4 and 8 km. The samples were collected bimonthly from October, 2002 to August, 2003. Some results match with the national and international standard characters while the other characters (Turbidity, total hardness, calcium, nitrate, phosphate and the biological oxygen demand values) were not match. The present study showed that drinking water treatment plant is undrinkable, as well as, the chlorine is not used in the plant, during study period